Applying team-based learning of diagnostics for undergraduate students: assessing teaching effectiveness by a randomized controlled trial study - Zeng, Rui (Adv Med Educ Pract, 2017)
BACKGROUND: We aimed to introduce team-based learning (TBL) as one of the teaching methods for diagnostics and to compare its teaching effectiveness with that of the traditional teaching methods. METHODS: We conducted a randomized controlled trial on diagnostics teaching involving 111 third-year medical undergraduates, using TBL as the experimental intervention, compared with lecture-based learning as the control, for teaching the two topics of symptomatology. Individual Readiness Assurance Test (IRAT)-baseline and Group Readiness Assurance Test (GRAT) were performed in members of each TBL subgroup. The scores in Individual Terminal Test 1 (ITT1) immediately after class and Individual Terminal Test 2 (ITT2) 1 week later were compared between the two groups. The questionnaire and interview were also implemented to survey the attitude of students and teachers toward TBL. RESULTS: There was no significant difference between the two groups in ITT1 (19.85±4.20 vs 19.70±4.61), while the score of the TBL group was significantly higher than that of the control group in ITT2 (19.15±3.93 vs 17.46±4.65). In the TBL group, the scores of the two terminal tests after the teaching intervention were significantly higher than the baseline test score of individuals. IRAT-baseline, ITT1, and ITT2 scores of students at different academic levels in the TBL teaching exhibited significant differences, but the ITT1-IRAT-baseline and ITT2-IRAT-baseline indicated no significant differences among the three subgroups. CONCLUSION: Our TBL in symptomatology approach was highly accepted by students in the improvement of interest and self-directed learning and resulted in an increase in knowledge acquirements, which significantly improved short-term test scores compared with lecture-based learning. TBL is regarded as an effective teaching method worthy of promoting.